PENGARUH KOMUNIKASI ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI BUDAYA ORGANISASI PADA DINAS PERTANIAN KABUPATEN KUTAI TIMUR - Nelly, Nelly (STIE Muhammadiyah Tanjung Redeb, 2017)
This study aims to determine the direct and indirect effect of organizational communication on the performance of employees through organizational culture at the Department of Agriculture of East Kutai Regency.Analysis tool that used in this study was multiple linear regression to know the correlation the influence of organizational communication (X) as Exogen variable, employee performance as Endogen variable (Y2) and organizational culture as Variable Mediation (Y1). The research instruments used are questionnaires, observations and interviews.The result of the research showed that organizational communication has a significant effect on employee performance, whereas organizational communication also has an effect on employee performance, and organizational culture has significant effect on employee performance, but organization communication has no significant effect on employee performance through organizational culture.